Journey And Pitstops Of Online Teaching And Learning: Enhancing The Learning Continuity Plan For The New Normal In Education - Arrieta, Gilbert S.; Sudarsana, I Ketut (LPM IHDN Denpasar, 2021)
Education is a physical and interactive human activity. Primarily, teachers and students meet and take part in various learning activities in school. Other educational activities are held outside the school to augment what is learned inside the school campus. When technology developed and made online education possible, it was not fully embraced because education is also a social activity. However, the Covid-19 pandemic forced everyone to do things online including education. Unprepared and untrained for this new learning modality, educators had to prepare for a short period of time. Teachers underwent training through online webinars and conferences, and learning continuity plan was developed. Online classes for academic year 2020-2021 started six months ago which revealed the strengths, weaknesses, challenges, and issues in online teaching and learning. This study aims to find out the challenges encountered by the school leaders, teachers, and academic in the implementation of the learning continuity plan for online education including the resolutions made to address the challenges. Based on the study, it was found out that formulation and implementation of new policies, technological resources and capability of teachers and students, mental health and concerns of teachers and students, communication with parents and students, and school requirements. Different resolutions were made that addressed the concerns. It also revealed that the learning continuity plan is responsive to online teaching and learning but there are components that need to be enhanced.